Lameness in Beef Cattle: UK Farmers' Perceptions, Knowledge, Barriers, and Approaches to Treatment and Control - Tunstall, Jay; Mueller, Karin; Grove White, Dai; Oultram, Joanne W. H.; Higgins, Helen Mary (Frontiers in Veterinary Science, 2019)
Lameness in the beef industry has received little attention in the UK, despite the fact that it is a well-recognised problem in the dairy industry. The aims of this study were to (i) compare UK beef farmers’ estimates of lameness prevalence to that of researchers, (ii) explore beef farmers’ attitudes towards lameness and (iii) help identify farmer reported barriers to lameness control and treatment. Beef farmers (11 finishing units and 10 suckler farms) were recruited from England and Wales. Farmers were asked to estimate their lameness prevalence, before a researcher conducted locomotion scoring using a five point scale, and a Bland Altman analysis performed. Face to face interviews were also conducted using a semi structured interview script aimed at capturing information such as current approaches and protocols as well as their views of lameness importance. Interviews were recorded and transcribed. An inductive thematic analysis was performed. All but two farmers underestimated lameness prevalence on their farms when compared to the researcher. Farmers initially underestimated lameness prevalence compared to the researchers estimates, with a mean underestimate of 7% (95% CI 5-9%). This is an important barrier to lameness detection and treatment. Thematic analysis identified four major themes: 1. Perception of lameness prevalence, 2. Technical knowledge and skills, 3. Perception of the impact of lameness and 4. Barriers to the treatment and control of lameness. This study highlights that some approaches to lameness treatment are likely to be causing harm, despite being done with the intention to help the animal. There were four key areas of concern identified: recognition of lameness, treatment approaches, the training provided to farmers and confusion over transport and slaughter options available to farmers. This suggests an urgent need for future work to quantify and then address the problem, and to provide evidence to justify the role of prevention and potentially start to break down barriers to control and treatment of lameness.